Preparation and evaluation of polymeric microparticulates for improving cellular uptake of gemcitabine - Lim JH (Dove Medical Press, 2012)
Ji-Ho Lim1,*, Sung-Kyun You1,*, Jong-Suep Baek1, Chan-Ju Hwang1, Young-Guk Na1, Sang-Chul Shin2, Cheong-Weon Cho11College of Pharmacy and Institute of Drug Research and Development, Chungnam National University, Gungdong, Yuseonggu, Daejeon, South Korea, 2College of Pharmacy, Chonnam National University, Buggu, Gwangju, South Korea *These authors contributed equally to this workBackground: Gemcitabine must be administered at high doses to elicit the required therapeutic response because of its very short plasma half-life due to rapid metabolism. These high doses can have severe adverse effects.Methods: In this study, polymeric microparticulate systems of gemcitabine were prepared using chitosan as a mucoadhesive polymer and Eudragit L100-55 as an enteric copolymer. The physicochemical and biopharmaceutical properties of the resulting systems were then evaluated.Results: There was no endothermic peak for gemcitabine in any of the polymeric gemcitabine microparticulate systems, suggesting that gemcitabine was bound to chitosan and Eudragit L100-55 and its crystallinity was changed into an amorphous form. The polymeric gemcitabine microparticulate system showed more than 80% release of gemcitabine in 30 minutes in simulated intestinal fluid. When mucin particles were incubated with gemcitabine polymeric microparticulates, the zeta potential of the mucin particles was increased to 1.57 mV, indicating that the polymeric gemcitabine microparticulates were attached to the mucin particles. Furthermore, the F53 polymeric gemcitabine microparticulates having 150 mg of chitosan showed a 3.8-fold increased uptake of gemcitabine into Caco-2 cells over 72 hours compared with gemcitabine solution alone.Conclusion: Overall, these results suggest that polymeric gemcitabine microparticulate systems could be used as carriers to help oral absorption of gemcitabine.Keywords: gemcitabine, polymeric microparticulates, mucoadhesive, enteric coating, cellular uptake, oral absorption